Novel DTC induction machine drive improvement using controlled rectifier for DC voltage tuning - Nour Mohamed; Tedjini Hamza; Gasbaoui Brahim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The application of the direct torque control strategy for induction machine drives is mainly characterized by torque and flux distortions caused by voltage vector limitation. The goal of this paper is to perform the conventional DTC induction machine drives and reduce ripples of both flux and torque response. The proposed contribution is based on the control of the DC output side of the rectifier feeding the voltage source inverter by means of PI controller in order to adapt the voltage vector used in typical DTC switching table. Mathematic models are built using MATLAB Simulink and programming environment; the simulation results show the difference between the proposed method and classical DTC.